Moving electrons captured by bright ultraviolet light. (Research'eu results magazine)
EU-funded scientists have demonstrated, for the first time, the generation of isolated attosecond pulses of unprecedented brightness in the extreme ultraviolet window. This achievement allows scientists to further explore ultrafast physics such as electron dynamics and quantum tunnelling.